We know what they did wrong, but not why: the case for 'frame‐based' feedback. (9th May 2013) - Rudolph, Jenny; Raemer, Daniel; Shapiro, Jo
Summary Background: Actionable feedback targeted to the learner's needs is one of the strongest predictors of improved performance in learning. Unfortunately, when a trainee makes an error, although instructors may understand what a trainee has done wrong, they can erroneously assume they know why. Context: There is a growing recognition that cognitive biases impede clinical diagnosis, however, the same biases can also undermine accurate and effective feedback. Innovation: Instead of focusing primarily on correcting actions, it is often crucial to diagnose trainees''frames'– the thought processes that drive their actions. We offer an efficient three‐step algorithm for providing this 'frame‐based' feedback: (1) describe how the trainee is doing according to the instructor; (2) diagnose the trainee's immediate learning needs using inquiry to elicit their frame; and (3) direct instruction to those needs. Implications: 'Misdiagnosis' of the trainee's actual needs wastes time when instructors teaching unneeded material, diminishes the trainee's faith in the value of instruction and undermines patient safety when incorrect frames about important clinical processes persist.